Prawne aspekty relacji działalności statutowej i gospodarczej fundacji: [Legal aspects of the relation between foundation’s statutory and business activity] (Studia Prawnicze / The Legal Studies, 2016)
Opracowanie na temat wzajemnej relacji działalności statutowej i gospodarczej fundacji przedstawił ponad 13 lat temu R. Trzaskowski i jest to najszersza dostępna w polskiej literaturze prawniczej analiza tego zagadnienia. Poza tym w komentarzach do ustawy o fundacjach (dalej u.f.) uwagi na temat stosunku działalności statutowej do gospodarczej pojawiają się w związku z art. 5 ust. 5 u.f., który stanowi, że fundacja może prowadzić działalność gospodarczą w rozmiarach służących realizacji jej celów. Z tego przepisu wyprowadza się zasadę, że działalność gospodarcza ma mieć stosunek służebny, akcesoryjny do działalności statutowej. Taki też można było nadać tytuł niniejszemu artykułowi: akcesoryjność działalności gospodarczej w stosunku do działalności statutowej fundacji. Jednak jak zostanie niżej wykazane, takie ujęcie jest zbyt dużym uproszczeniem. Można już mieć wątpliwości co do tego, czy samo sformułowanie „rozmiar służący realizacji celów” musi oznaczać służebność, czyli stan podporządkowania, a jeśli nawet tak, to jak to podporządkowanie rozumieć? Rozbieżność w tym zakresie uzasadnia potrzebę powrotu czy raczej kontynuacji tego tematu. This article presents the influence of foundation’s business activity on its statutory objectives. According to the Law on Foundations of April 6, 1984 ,the foundation may conduct business activity only to serve it’s statutory objectives, what used to be interpreted as the accessory rule of foundation’s business activity to its statutory activity. However in a foundation with both public and private benefit objectives, business activity may be one of the statutory goals. Furthermore the expanses on the business activity tend to dominate those on statutory goals. Both activities are conducted on the same field, by the same people, using the same equipment, so they are mixed within the same organizational framework.Foundation conducting business activity is an entrepreneur with all consequences, for the most such as becoming the subject of insolvency proceedings. However the Law on Foundations creates no legal tools to properly establish foundation on the field of business activity especially when it comes to management liability and supervision. Analysing and summing up all those problems has led me to introduce the concept of the new regulation on foundation law in Poland. The idea is to divide foundations into two categories: charitable (noncommercial) and commercial. The second type of foundations could be an interesting alternative for those entrepreneurs, who want to run their activity on the capital, not corporate, basis.